Avaliação dos teores de metais em solos, plantas e sedimento aderido às raízes do sistema várzea-estuário dos igarapés Piraíba e Anani Distrito Industrial de Icoaraci, Belém-PA - Cunha, Débora Suely Anjos da (Museu Paraense Emílio Goeldi, 2023)
The present work studied the soil and vegetation of the Píraíba and Anani streams, located in the floodplain-estuary-mangrove system of Furo do Maguari (Icoaraci/Belém) and receptors of the local lumber and tannery activities, with the objective of determining the metal contents in sediments adhered to the root and soil and in the leaves of the following plant species:Euterpe Oleracea. Mart (Açaí); Montrichardia arborescens. L (Aninga) and Crinum Undulatum. Collections were made at four points in the Píraíba River and three points in the Anani River. In the wet season, both streams presented higher acidity at the points near the logging sites. The soil profiles of Piraíba creek are in general reduced and oxidizing in the superficial layers. The lowest Eh values were found near the logging site. In the Anani stream near the mouth the environment is reductive, while near the logging site the environment becomes oxidizing in depth. In the dry period the points of the logging sites for both streams proved to be less acidic and reductive, but in the Píraíba near the logging site it is oxidizing. In the rainy period, the highest calcium values were in the leaves and magnesium shows higher values in the soil. The chromium values in Piraíba creek are much higher than in Anani creek for all species. The species with the highest chromium values was the açaí